طرائق تعليم الإملاء لترقية كفائة الكتابة للطلبة في المعهد: (Teaching Methods of Dictation to Improve Writing Skills for Students at Islamic Boarding School) - Ahmad Fikri Amrullah; Muhammad Syahrul Munir (STAI Ma'had Aly Al-Hikam Malang, 2025)
Abstract The teaching of Arabic language began in Indonesia a long time ago, when Islam entered this country, and we learn this language as the language of the Islamic Religion, then it is taught in schools and boarding schools, both under the supervision of the Ministry of Religion. Ministry of Education and Culture, both government and local. For good Arabic teaching, the teacher must pay attention to and think about the curriculum and teaching methods used in teaching Arabic language, because both are two means of success in the learning process along with other factors. Many Arabic teachers don't really care about Arabic teaching methods. There are many schools and schools of Islamic education in Indonesia that revolve around the advancement of science and technology or philosophy, psychology and sociology so that Muslims who come are not late for things they will accept and explain in their future lives. Among them is Al-Kamal Islamic Boarding School Kunir Blitar. This doctoral dissertation aims to reveal and find out the steps used in learning imla at Al-Kamal Islamic Boarding School Kunir Blitar, to reveal and find out the steps used to teach vocabulary at Al-Kamal Islamic Boarding School Kunir Blitar. Detect and find out about the method used to teach superposition at Al-Kamal Islamic Boarding School Kunir Blitar.The results of this study are: The steps used for learning dictation are: Al-Kamal Islamic Boarding School Kunir Blitar uses the method, listen, read and write for dictation letters, sentences and essay. The steps used for teaching vocabulary are: starting from the dormitory by giving vocabulary every day after the morning prayer. Each student repeats what the language movement from each dormitory says and writes it down and orders them to memorize it and put the vocabulary in sentences and continue teaching it in class according to their respective classes. and writing vocabulary in several places according to their vocabulary. The steps used for superposition learning at Al-Kamal Islamic Boarding School Kunir Blitar, the teacher starts writing examples on the blackboard then asks the lesson of yesterday's lesson and explains the relationship between yesterday's lesson and the new lesson and explains the rules of nahwu science and shorof by example. Keywords: Teaching Methods, Writing Skills